Structural analysis of lexical bundles in university lectures of politics and chemistry - Kashiha, Hadi; Chan, Swee Heng (Australian International Academic Centre, 2014)
Referred to as extended collocations, lexical bundles are considered as a main factor in building fluency in academic discourse; helping to shape meaning and coherence in a text or speech. For decades, lexical bundles have attracted considerable amount of attention in corpus-based research in English for Academic Purposes (EAP). While, the focus of the most of the studies on lexical bundles was to explore the use of these multi-word expressions in academic written registers such as research articles, academic spoken registers such as university lectures have not received that amount of attention from the scholars. In this vein, there is still an open question of how they are structurally different across disciplines. With these concerns in mind, this study aimed to explore how lexical bundles are used structurally in a 50291 words corpus of 8 university lectures across two disciplines: chemistry and politics. To this aim, the most frequent four-word bundles in the corpus were classified according to their grammatical types to see the possible disciplinary variations in their frequency of use as well as the structure involved in their use. Results of the analysis revealed that noun phrase and prepositional phrase fragments were the most common structures in the lectures of the two disciplines, accounting for more than half of the bundles in politics. University lecturers appear to apply a variety of structures in the use of lexical bundles often peculiar to the discipline in order to convey their disciplinary messages. This would lead to the need to emphasize the instruction of the most common structures in that discipline in a way for the lectures to be as comprehensive as possible for the intended audiences.